Sales levels and asset confiscation penalty among commerce sector taxpayers in Peru - Llave Angulo, Irvin Luis (2023)
Objective: Determine the relationship between the sales level and the asset confiscation penalty for taxpayers in the commerce sector in Peru during the period 2013-2020. Methods: The approach was quantitative, relational, with a non-experimental design, and an applied nature. An investigation was conducted through the documentary analysis of reports obtained from National Superintendency of Customs and Tax Administration. The relationship between the sales level declared by taxpayers and the levels of asset confiscation penalties imposed during the period 2013-2020 was evaluated using the Spearman’s Rho correlation coefficient. Results: There is a significant inverse relationship between the sales levels declared by taxpayers and the asset confiscation penalty for not having payment receipts in the interventions carried out by the Tax Administration. Conclusion: In the short term, lower sales levels are associated with a higher probability of committing the offense of not carrying the payment receipt that supports the ownership and/or possession of the goods transported by the taxpayer. This is explained by a weak tax culture and a lack of awareness of the obligation to contribute to the tax authorities.